2019
DOI: 10.35609/jmmr.2019.4.1(11)
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Effect of Transfer Climate on the Joint Relationship between Trainees' Personality and Transfer Training

Abstract: Objective - The aim of this study is to examine the joint relationship between the Big Five personality and transfer climate on transfer of training. Drawing on trait activation theory, this study examines how the relationship between Big Five personality and transfer of training is moderated by supervisor support and opportunity to perform. Methodology/Technique - The sample of this study consists of 183 police officers who have attended driver training in one of the police training centres in Malaysia. Thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Goal orientation is a mental framework that affects how individuals interpret and react during learning opportunities (Chiaburu & Marinova, 2005;Chiaburu & Tekleab, 2005;Ford et al, 2018;Ford et al, 1998) Personality Individual characteristics (e.g., conscientiousness, extraversion, agreeableness, curiosity, humility, and resilience) influence the extent that trainees exhibit the trained KSAs on the job (Eid & Quinn, 2017;Ford et al, 2018;Ng & Ahmad, 2018;Yee, 2019)…”
Section: Goal Orientationmentioning
confidence: 99%
See 1 more Smart Citation
“…Goal orientation is a mental framework that affects how individuals interpret and react during learning opportunities (Chiaburu & Marinova, 2005;Chiaburu & Tekleab, 2005;Ford et al, 2018;Ford et al, 1998) Personality Individual characteristics (e.g., conscientiousness, extraversion, agreeableness, curiosity, humility, and resilience) influence the extent that trainees exhibit the trained KSAs on the job (Eid & Quinn, 2017;Ford et al, 2018;Ng & Ahmad, 2018;Yee, 2019)…”
Section: Goal Orientationmentioning
confidence: 99%
“…In fact, empirical evidence has demonstrated that individuals with higher self-efficacy and motivation will exhibit better job performance (Na-Nan & Sanamthong, 2020). In addition, individual personality traits, such as conscientiousness, extraversion, and agreeableness, have been associated with training transfer (Ng & Ahmad, 2018; Yee, 2019). Conscientiousness is linked to transfer in that it relates to being persistent and goal-directed, and extraversion is associated with training transfer because extraverts are characterized as being ambitious, active, and motivated.…”
Section: Introductionmentioning
confidence: 99%